2010
DOI: 10.1111/j.1467-9663.2010.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Resident Perceptions of Flagship Waterfront Regeneration: The Case of the Kop Van Zuid in Rotterdam

Abstract: Flagships, also referred to as megaprojects, and frequently involving waterfront regeneration, are a common form of urban redevelopment. Their goals are often aimed at an outside audience of tourists, investors and potential (high income) residents. While the target may be external, the ways in which these spaces are perceived by the local population is an important, and, as yet, under-researched, area. Many scholars suggest that flagships have a negative impact on cities, but their research stops short of ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 38 publications
1
53
1
3
Order By: Relevance
“…This is not totally surprising, as Bridge and Dowling (2001) conclude that retails spaces in gentrified areas represent the identities and consumption patterns of gentrifiers themselves. However, our findings in Dublin run counter to Doucet et al's (2011b) work on Rotterdam, which showed that low-income residents appreciated the amenities in Rotterdam's prestigious Kop van Zuid flagship waterfront project. This was due to the fact that Rotterdam's flagship had the type of stores and services such as affordable supermarkets and other 'basic' services which were being called for by Sheriff Street residents.…”
Section: Resultscontrasting
confidence: 84%
“…This is not totally surprising, as Bridge and Dowling (2001) conclude that retails spaces in gentrified areas represent the identities and consumption patterns of gentrifiers themselves. However, our findings in Dublin run counter to Doucet et al's (2011b) work on Rotterdam, which showed that low-income residents appreciated the amenities in Rotterdam's prestigious Kop van Zuid flagship waterfront project. This was due to the fact that Rotterdam's flagship had the type of stores and services such as affordable supermarkets and other 'basic' services which were being called for by Sheriff Street residents.…”
Section: Resultscontrasting
confidence: 84%
“…Following is a discussion of the circumstances which may both trigger and influence the exercise of power, based on the cruise infrastructure's stage of development. Cruise destinations can use or reuse urban land for marine activities (including for the development of cruise infrastructure) that has been deemed to be desirable, capable of attracting investors and potential residents as well as tourists (Doucet et al, 2010). Additionally, cruise terminals in particular are often perceived by local policy makers and planners as a means for strengthening a destination's competitiveness in a global environment where competition between cities becomes increasingly intense (McCarthy & Romein, 2012).…”
Section: Stage Of Development: Proposed Mature and Declining Cruise mentioning
confidence: 99%
“…Estas políticas, desplegadas por las diferentes Administraciones Públicas, se pueden considerar como pauta habitual, como parte de una activa implementación de políticas neoliberales de gentrifi cación y como un medio para requerir la ciudad para los negocios, la clase media y las fuerzas del mercado en general (Peck, 2006: 681). Tales políticas públicas se ejemplifi can en los partenariados público-privados como los destinados a la regeneración de las zonas portuarias (Butler, 2007;Doucet et al, 2011a;2011b), la recuperación de antiguas zonas industriales (Díaz Orueta y Fainstein, 2009), o la renovación de los centros históricos para satisfacer las demandas de los consumidores de clase media y alta (Zukin, 1998). En todos estos casos, el Estado no solo organiza activamente la desposesión de los hogares de menores ingresos, sino que también implementa una poderosa estrategia discursiva para ocultar cualquier interpretación de su propia acción como parte de una agresiva ideología revanchista, diseñada para reconquistar el centro de la ciudad para las clases medias (Lees, 2008).…”
Section: Los Discursos Convencionales De Gentrifi Cación Y El Estudiounclassified